Perspectives in solubility measurement and interpretation - Christel A.S. Bergström; Alex Avdeef (International Association of Physical Chemists (IAPC), 2019)
Several key topics in solubility measurement and interpretation are briefly summarized and illustrated with case studies drawing on published solubility determinations as a function of pH. Featured are examples of ionizable molecules that exhibit solubility-pH curve distortion from that predicted by the traditionally used Henderson-Hasselbalch equation and possible interpretations for these distortions are provided. The scope is not exhaustive; rather it is focused on detailed descriptions of a few cases. Topics discussed are limitations of kinetic solubility, 'brick-dust and grease-balls,' applications of simulated and human intestinal fluids, supersaturation and the relevance of pre-nucleation clusters and sub-micellar aggregates in the formation of solids, drug-buffer/excipient complexation, hydrotropic solubilization, acid-base 'supersolubilization,' cocrystal route to supersaturation, as well as data quality assessment and solubility prediction. The goal is to highlight principles of solution equilibria - graphically more than mathematically - that could invite better assay design, to result in improved quality of measurements, and to impart a deeper understanding of the underlying solution chemistry in suspensions of drug solids. The value of solid state characterizations is stressed but not covered explicitly in this mini-review.